Effects of alcohol on hypertension and nursing practice - Grabowska, Hanna; Grabowski, Władysław; Nowakowska, Halina; Gaworska-Krzemińska, Aleksandra; Narkiewicz, Krzysztof (Nursing Problems / Problemy Pielęgniarstwa, 2012)
Excessive alcohol consumption is among the primary factor contributing to the development of arterial hypertension. The current view is that alcohol can be responsible for several to over a dozen percent of all cases of primary hypertension. One of the strategies aimed at alleviating the damage caused by alcohol consumption (including the appearance of hypertension) is the popularization of knowledge about the impact of alcohol consumption on human health, prevention and methods of detecting excessive alcohol consumption issues among health care employees. The aim of this article is to show the influence of alcohol consumption as on blood pressure and the risk of hypertension development, and to demonstrate the possibility of assessing the amount of alcohol intake by patients in nursing practice.